2022
DOI: 10.3390/en15186609
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Lightning Overvoltage in Unmanned Aerial Vehicles

Abstract: This paper presents research on the model developed in the Matlab environment for simulating effects of overvoltage in an unmanned aerial vehicle (UAV) upon lightning discharge. They are based on transmittance obtained from voltage surge impulse measured in drone circuits. Overvoltage waveforms were measured at the input and output of different parts of the machine. It was then possible to calculate the transmittance of those (chosen) circuits. The motors, supply system, communication lines, and sensors were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…High voltage direct current (HVDC) Tx lines and high voltage alternating current (HVAC) lines with potential exceeding 69kV AC emit high intensity E/H fields, with interference effects scaling nonlinearly with proximity [3]- [6]. Particularly, studies have empirically shown that E/H field strengths above 3-5kV/m can materially impact UAV orientation sensors and flight control response [7].…”
Section: Introductionmentioning
confidence: 99%
“…High voltage direct current (HVDC) Tx lines and high voltage alternating current (HVAC) lines with potential exceeding 69kV AC emit high intensity E/H fields, with interference effects scaling nonlinearly with proximity [3]- [6]. Particularly, studies have empirically shown that E/H field strengths above 3-5kV/m can materially impact UAV orientation sensors and flight control response [7].…”
Section: Introductionmentioning
confidence: 99%